Mechanical force promotes tissue and molecular changes in adipose tissue regeneration post-transplantation - Ye, Yuan; Ma, Jian; Guo, Bing-yang; Li, Xiong-jie; Hu, Kui-kui; Tan, Mei-jun; Zhang, Liang (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Fat grafting often yields inconsistent and suboptimal results, necessitating improved fat processing techniques. A stromal vascular fraction (SVF) gel created using mechanical emulsification demonstrates superior retention rates to conventional Coleman fat grafts.This study investigated the mechanisms at play by transplanting fat aspirates from liposuction patients-either processed as Coleman fat grafts or further refined into an SVF gel via mechanical shear force-onto the backs of nude mice.The retention rate of the SVF gel after transplantation surpassed that observed for Coleman fat. Hematoxylin and eosin (HE) staining and immunofluorescence results demonstrated that the SVF gel group could form new adipose tissue characterized by well-organized mature fat structures. Mechanical shear force application induced increased mesenchymal stem cell abundance. Rather than merely surviving regeneration, fat was regenerated after transplantation, and the regenerated cells were mainly from mice, which was supported by microarray analysis. RNA-seq highlighted 601 genes expressed between SVF gel and Coleman fat groups, with 164 genes upregulated (cell cycle processes), and 437 genes downregulated (lipid metabolism).Discussion: The application of mechanical shear force reduces the risk of complications and fosters cell proliferation and division, thereby enhancing the retention and regeneration of transplanted fat.